Applications of Declarative Programming and Knowledge Management: proceedings of the 18th International Conference, INAP 2009 - Abreu, Salvador (2012)
This volume contains a selection of papers, revised and extended, which were presented at the 18th International Conference on Applications of Declarative Programming and Knowledge Management, INAP 2009, which was held in Évora, Portugal, from November 3rd to 5th, 2009.